ANALISIS HUMAN DEVELOPMENT INDEX DAN ISLAMIC HUMAN DEVELOPMENT INDEX SEBAGAI PENGUKUR SUMBER DAYA INSANI DI INDONESIA - Annisa Masruri Zaimsyah (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
The purpose of this paper is to analyze the comparison of I-HDI and HDI as a measure of Human Resources in Indonesia. The I-HDI measurement is based on the five elements of Maqasid Syariah. The method in this research is a qualitative method with a descriptive approach by collecting data through the literature and analyzing it to reach a conclusion. The results show that I-HDI can measure Human Resources, human resources in Indonesia in the process of achieving the five elements of Maqasid sharia. Elements that must be fulfilled to maintain basic needs aimed at happiness in this world and the hereafter. So it is necessary to instill the qualities of Siddiq, Amanah, Fatanah, Tabligh and Istiqamah. The implication of this research is that measuring human resources can be done through I-HDI so that by increasing I-HDI the quality of human resources will increase.